Strategi Pengelolaan Tanah Kas Desa dalam Mewujudkan Desa Mandiri di Desa Wunut - Muhammad Aniq Fadhilah; Setiowati; R. Deden Dani Saleh; Aristiono Nugroho (Kadaster: Journal of Land Information Technology, 2026)
Village administration plays a vital role in national development, aligning with the 6th Asta Cita and the Village Law. However, the management of village treasury lands generally remains hindered by a lack of innovation and integrity. In contrast, Wunut Village in Klaten Regency has successfully optimized its treasury land into a productive tourism sector. This qualitative research aims to analyze Wunut Village's management strategies and their impact on achieving "Independent Village" status, using participatory theory as an analytical framework. Data were collected through interviews, observations, and documentation, then systematically analyzed through data reduction and abstraction to formulate propositional statements. The results indicate that the key to Wunut Village's success lies in full community involvement, from planning to oversight. Challenges such as initial public skepticism were overcome through deliberation, budget transparency, and the spirit of mutual cooperation. The direct impact of this success is evident in social benefits, such as providing health insurance coverage for all residents. This achievement transformed Wunut from a disadvantaged village into an Independent Village with the highest Original Village Income (PADes) in Klaten Regency as of 2025. This strategy proves that village autonomy, when managed with integrity, can effectively realize economic equity and community welfare. Keywords: Management, Participatory, Village Treasury Land, Village Original Income, Self-Sufficient Village.   INTISARI Desa memegang peran vital dalam pembangunan nasional sesuai semangat Asta Cita ke-6 dan UU Desa. Namun, pengelolaan tanah kas desa secara umum masih terkendala kurangnya inovasi dan integritas. Kontras dengan kondisi tersebut, Desa Wunut di Kabupaten Klaten berhasil mengoptimalkan tanah kas desa menjadi sektor pariwisata produktif. Penelitian kualitatif ini bertujuan menganalisis strategi pengelolaan tanah kas Desa Wunut dan dampaknya terhadap status Desa Mandiri menggunakan teori partisipatif. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis secara sistematis. Hasil penelitian menunjukkan bahwa kunci keberhasilan Desa Wunut terletak pada keterlibatan penuh masyarakat dalam perencanaan hingga pengawasan. Tantangan berupa keraguan warga diatasi melalui musyawarah, transparansi anggaran, dan gotong royong. Dampak nyatanya mencakup pemberian bantuan BPJS Kesehatan bagi seluruh warga. Keberhasilan ini mentransformasi Desa Wunut dari desa tertinggal menjadi Desa Mandiri dengan Pendapatan Asli Desa (PADes) tertinggi di Kabupaten Klaten pada tahun 2025. Strategi ini membuktikan bahwa otonomi desa yang dikelola dengan integritas mampu mewujudkan pemerataan ekonomi dan kesejahteraan masyarakat. Kata Kunci: Pengelolaan, Partisipatif, Tanah Kas Desa, Pendapatan Asli Desa, Desa Mandiri